Treatment of well-differentiated invasive squamous cell carcinoma of the skull and reconstruction by ultrathin anterolateral thigh flap - Ramírez, Eduardo D.; Mendoza, Jose B.; Ugalde, Juan A.; Ríos, Rodolfo L.; Canepa, Patricio; Perrusquia, Daniela (International Journal of Research in Medical Sciences, 2025)
Invasive squamous cell carcinoma is an aggressive form of skin cancer that requires radical surgical treatment and reconstruction. This article presents a clinical case of a 74-year-old patient with well-differentiated invasive squamous cell carcinoma of the skull, treated with surgical resection and reconstruction using an ultrathin anterolateral thigh flap. Reconstruction with an ultrathin anterolateral thigh flap is an effective therapeutic option that can offer numerous benefits and advantages for patients, improving their quality of life and their ability to carry out daily activities. This reconstructive technique allows for the restoration of the shape and function of the skull and face, minimizes morbidity and complications, and enhances facial aesthetics. Timely and effective treatment of invasive squamous cell carcinoma through reconstruction with an ultrathin anterolateral thigh flap can significantly improve the patient’s survival and quality of life. In conclusion, the ultrathin anterolateral thigh flap is an excellent reconstructive option for patients with scalp defects secondary to extensive oncological resections.